FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PROBABILITAS WANITA BEKERJA DI PROVINSI SUMATERA BARAT - Dini Rahim; Syamsul Amar; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2018)
This study aims to determine the effect of age, marital status, level of education, area of residence, number of dependents, family expenses, and head of household status on the probability variable of women choose to be a working women in West Sumatra Province. This is descriptive and associative research, where the data used is secondary data in the form of cross-section data. The data was from national socioeconomic survey in 2016. By using logistic regression, the results of this study show that the variables of age, marital status, level of education, and number of dependents have a positive and significant effect on probability of women working in West Sumatra, while the variable area of residence has a negative and significant influence on probability of women working in West Sumatra province.